PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS, DAN UMUR PERUSAHAAN TERHADAP KELENGKAPAN PENGUNGKAPAN LAPORAN KEUANGAN - Eka Mega Puspita Rahayu, 13.05.52.0022; Indarti, MG. Kentris (Students' Journal of Accounting and Banking, 2017)
The purpose of this research is to analyze profitability, leverage, liquidity, and age company to completeness of financial statement disclosure. This research was conducted at the Indonesian Stock Exchange by using analysis unit LQ 45 companies. Research period start on 2013-2015 years. Data used in this research is secondary data, the data in this study were obtained from the Financial Statements and ICMD (Indonesian Capital Market Directory) 2013-2015. The sampling method used is purposive sampling. The amount of data that is processed as many as 122 companies. Methods of data analysis using multiple linear regression. The results of research showed that liquidity and age of company has effect on completeness of financial statement disclosure while profitability, leverage has no effect completeness of financial statement disclosure.Keywords: Profitability, Leverage, Liquidity, Age Company, and Completeness of Financial Statement Disclosure